The finished result.
Shelf no.
This Rendile elder shows a perfect peri-umblilical cicatrix,a transv erse elliptical,slightly raised,hyperpigmented plaque with a sharply de lineated central hole.He also shows nice decoration scars on bell and chest,and wears two amulets in his beads.30 miles North of Marabit.
AR/MAK PHOTOS/21/2
English
Keywords: Photos of Kenya